PENINGKATAN MUTU PENDIDIKAN MELALUI OPTIMALISASI SISTEM ADMINISTRASI PENDIDIKAN DI YAYASAN PENDIDIKAN ISLAM AN-NUR - Mursal Aziz; Muhammad ‘Arif; Muhammad Fiqri Alwi; Mhd Nuryansah Nugraha (STKIP Subang, 2024)
This research aims to evaluate improving the quality of education through the administration system at the institution. This research uses qualitative descriptive methods to collect descriptive data, both verbal and written, about individuals and observed behavior. Quality education requires various factors such as subject matter (cognitive, emotional and psychomotor), technology, school facilities, administrative facilities and other resources, as well as creating a conducive learning environment. The quality of education is measured by the achievements achieved by the school at a certain time, for example through academic and non-academic aptitude tests. Academic success can also be influenced by non-physical factors such as a school culture that promotes discipline, cooperation, mutual respect and a clean spirit. However, the implementation of the administration system at Madrasah Ibtidaiyah An-Nur is still not optimal. Many teachers have not been fully able to carry out their administrative responsibilities, with some postponing work until after the learning session. Several factors inhibiting reaching its maximum potential include low student motivation, suboptimal human resources, low teacher discipline, and limited funding for madrasas.